Sweet complexity: O-linked protein glycosylation in pathogenic Neisseria - Børud, Bente; Koomey, Michael (Frontiers in Cellular and Infection Microbiology, 2024)
The genus Neisseria, which colonizes mucosal surfaces, includes both commensal and pathogenic species that are exclusive to humans. The two pathogenic Neisseria species are closely related but cause quite different diseases, meningococcal sepsis and meningitis (Neisseria meningitidis) and sexually transmitted gonorrhea (Neisseria gonorrhoeae). Although obvious differences in bacterial niches and mechanisms for transmission exists, pathogenic Neisseria have high levels of conservation at the levels of nucleotide sequences, gene content and synteny. Species of Neisseria express broad-spectrum O-linked protein glycosylation where the glycoproteins are largely transmembrane proteins or lipoproteins localized on the cell surface or in the periplasm. There are diverse functions among the identified glycoproteins, for example type IV biogenesis proteins, proteins involved in antimicrobial resistance, as well as surface proteins that have been suggested as vaccine candidates. The most abundant glycoprotein, PilE, is the major subunit of pili which are an important colonization factor. The glycans attached can vary extensively due to phase variation of protein glycosylation (pgl) genes and polymorphic pgl gene content. The exact roles of glycosylation in Neisseria remains to be determined, but increasing evidence suggests that glycan variability can be a strategy to evade the human immune system. In addition, pathogenic and commensal Neisseria appear to have significant glycosylation differences. Here, the current knowledge and implications of protein glycosylation genes, glycan diversity, glycoproteins and immunogenicity in pathogenic Neisseria are summarized and discussed.